Assessing The Impact of Tourism Ban on Ecosystem Recovery in Saint Martin Marine Protected Area, Bangladesh - Rahman, Rezaur; Azam Chowdhury, K. M.; Kibria, Mirza Golam; Capuano, Tonia Astrid (Journal of Environmental Management and Tourism; Vol 17 No 2 (2026): JEMT, Volume XVII, Issue 2(82), Summer 2026DO - 10.14505/jemt.v17.2(82).06, 2026)
Situated in the north-eastern Bay of Bengal, Saint Martin’s Island is a small sedimentary island. It hosts the only coral ecosystem in Bangladesh and is popularly (but wrongly) called ‘coral island’. Since 2004, uncontrolled tourism and unsustainable practices, along with global warming and marine pollution have considerably degraded island’s ecosystems and threatened its very existence. To mitigate this substantial threat, in January 2022, Bangladesh Government declared Saint Martin Marine Protected Area and in October 2024, imposed strict tourism regulations including a ‘nine months’ tourism ban’ on the island, generating mixed reactions. Amid opposing demands from environmental and hospitality stakeholders, the first-ever ‘tourism ban’ (February to October 2025) has come to an end, providing a unique opportunity to assess the health status of the marine ecosystem and eventual recovery. For this purpose, temperature, salinity, pH, dissolved oxygen, total dissolved solids and turbidity were measured from November 2022 to October 2025, using multi-parameter oceanographic instruments. While the assessment of temperature and salinity showed distinct seasonal variability, the comparison of other bio-geochemical parameters, before and during the ‘nine months’ tourism ban’, demonstrated considerable ecological improvement (DO improved from 6.0-6.6 to 7.1-7.4 mg/L and pH improved from 7.0-8.14 to 8.13-8.21). As one of the first in-situ assessments in the Bay of Bengal region, linking ‘tourism ban’ with ecosystem recovery, this research has the potential to generate valuable insights for sustainable development in Saint Martin’s Island and similar places across the globe.